2013
DOI: 10.1007/s11103-013-0079-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of stable, high copy number, medium-sized RNA degradation intermediates that accumulate in plants under non-stress conditions

Abstract: It is becoming increasingly evident that the RNA degradome is a crucial component of the total cellular RNA pool. Here, we present an analysis of the medium-sized RNAs (midi RNAs) that form in Arabidopsis thaliana. Our analyses revealed that the midi RNA fraction contained mostly 20–70-nt-long fragments derived from various RNA species, including tRNA, rRNA, mRNA and snRNA. The majority of these fragments could be classified as stable RNA degradation intermediates (RNA degradants). Using two dimensional polyac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 49 publications
(97 reference statements)
5
35
0
Order By: Relevance
“…52 Notably, stress granules have still been observed even in the case YB-1 was removed by RNAi, thus leaving many mechanistic questions still unanswered how 5′ tRNA halves are involved in translation control. Similar inhibitory effects of 5′ tRNA halves on translation were recently observed in the plant Arabidopsis thaliana, 27 but with some notable differences: (1) diverse tRNA pieces, including tRNA halves, have been observed independent of stress and, (2) the inhibitory effect of the 5′ tRNA halves on in vitro translation did not correlate with the number of consecutive guanine residues at the 5′ end as proposed by Anderson et al Furthermore, it was demonstrated that the human tRNA halves (Ala/Cys), which repressed translation initiation in rabbit reticulocyte lysate, 52 showed no inhibitory effect in wheat germ extract. This either hints to species specificity or to missing cofactors that determine the inhibitory potential.…”
Section: Trna In Piecessupporting
confidence: 78%
See 4 more Smart Citations
“…52 Notably, stress granules have still been observed even in the case YB-1 was removed by RNAi, thus leaving many mechanistic questions still unanswered how 5′ tRNA halves are involved in translation control. Similar inhibitory effects of 5′ tRNA halves on translation were recently observed in the plant Arabidopsis thaliana, 27 but with some notable differences: (1) diverse tRNA pieces, including tRNA halves, have been observed independent of stress and, (2) the inhibitory effect of the 5′ tRNA halves on in vitro translation did not correlate with the number of consecutive guanine residues at the 5′ end as proposed by Anderson et al Furthermore, it was demonstrated that the human tRNA halves (Ala/Cys), which repressed translation initiation in rabbit reticulocyte lysate, 52 showed no inhibitory effect in wheat germ extract. This either hints to species specificity or to missing cofactors that determine the inhibitory potential.…”
Section: Trna In Piecessupporting
confidence: 78%
“…The generated 3′ tRFs seem to be the result of global tRNA cleavage, induced by different stress stimuli (e.g., encystation, serum deprivation, cold stress, and heat shock). 82 tRFs of aberrant size and yet unknown function have also been detected in other studies, including 3′ quarters of tRNAs 27 and "mid"-fragments. 83 While most of the so far identified tRFs derive from mature tRNAs (with the exception of 3′U tRFs), Hanada et al recently reported on novel tRFs originating from aberrant pre-tRNA splicing.…”
Section: Unclassified Trfssupporting
confidence: 68%
See 3 more Smart Citations